Disposal of hospital wastage in Pakistan: A qualitative research - Fatima, Syeda Zain; Asad, Muzaffar (Advances in Social Sciences Research Journal, 2018)
Disposal waste process of Hospitals faced the different issues which raise the questions after the visit of government the hospitals in Punjab of Lahore. This study is used to aware about the issues about the infection wastage which cause about the different disease in Patients. This study is used to aware about the situation the government teaching hospitals of the waste management. In depth interviews conducted by 3 selected hospitals of Punjab Lahore like Jinnah Hospital Lahore, Service Hospital Lahore and Mayo hospital of Lahore from respondents include Medical Superintendent, Executive Director, Deputy Director, Nursing Superintendent and Focal Medical Officer which dealing with the waste management. Main gap which occur in the hospitals about the collection of the wastage and cleanliness of the hospitals. These problems occur by the less trained staff, weak monitoring and different issues which linked with the all staff members. Main results evaluate that to improve the waste management staff members in teaching hospitals of Lahore. The material of this study is, consequently, very essential for development and executing disposal of waste management program by any hospital. Proper distribution of budget and prearrangement of infectious waste management training at any hospital should be spelled out in health policy. A continuous supervision and monitoring could increase the motivation of health staff and ultimately affects their better working output on time.